Colors of Rhetoric in Holy Qura’an: (Surah Al-Ma’idah) - Amansaf, Abbas Kadhim (Al-Adab Journal, 2022)
This research deals with the colors of Al-Badi in Surat Al-Maedah, through the two sections upon which the rhetorical research on the science of Al-Badi'i was settled, namely the moral colors of Al-Badi and the verbal colors of Al-Badi; As for the morale’s moral colors; The researcher examined the counterpoint, the interview, observance of the counterpart and good division. As for the verbal colors of Badi, he addressed G = in which the researcher has three types, which are alliteration, both types and the recitation and miraculous response to the breasts. Quranic study and analysis.